PENGARUH CAPACITY BUILDING DAN REWARD TERHADAP KOMITMET KERJA SERTA IMPLIKASINYA PADA PRESTASI KERJA KARYAWAN - CHAIRIL GUNADHARMA (STIE Indonesia Malang, 2018)
Analytical tools used in this study is the analysis of the Path with the help of application Statistical Programme for Social Science (SPSS) Amos 23, whereas the sample used in this study were 72 employees contract which is the power seller in PT Danareksa securities.From the results of this research are expected to be known the extent to which the magnitude of influence between the variable Capacity Building and Reward employees with Work Performance against the Commitments of Work as intervening in PT Danareksa securities.Keywords:Capacity Building,Reward,CommitmentsofWorkand Work Performance